2016
DOI: 10.5267/j.ijiec.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Integrated batch production and maintenance scheduling for multiple items processed on a deteriorating machine to minimize total production and maintenance costs with due date constraint

Abstract: This paper discusses an integrated model of batch production and maintenance scheduling on a deteriorating machine producing multiple items to be delivered at a common due date. The model describes the trade-off between total inventory cost and maintenance cost as the increase of production run length. The production run length is a time bucket between two consecutive preventive maintenance activities. The objective function of the model is to minimize total cost consisting of in process and completed part inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…Let i th be the batch processed on the first machine with quantity Q[i11]. According to Halim and Ohta (1994), Yusriski et al (2015), Zahedi et al (2016) and Prasetyaningsih et al (2016) then in the process of batch inventory holding cost and completed batch inventory holding cost until the batch is processed on the second machine we have:…”
Section: Decision Variablesmentioning
confidence: 99%
“…Let i th be the batch processed on the first machine with quantity Q[i11]. According to Halim and Ohta (1994), Yusriski et al (2015), Zahedi et al (2016) and Prasetyaningsih et al (2016) then in the process of batch inventory holding cost and completed batch inventory holding cost until the batch is processed on the second machine we have:…”
Section: Decision Variablesmentioning
confidence: 99%
“…The result indicated that the proposed cyclic economic lot-scheduling structure can be resolved in a decomposed way, and the solution can be put in use easily and also can be adjusted to deal with bounded stochastic demands. Additional papers [16][17][18][19][20][21][22][23][24][25] also studied different characteristics of multi-item manufacturing systems.…”
Section: Introductionmentioning
confidence: 99%
“…AFT performance was used, adopting a backward scheduling approach in order to minimize the time of the parts flowing in both stages and meet the due date simultaneously. AFT performance has been applied in [14][15][16] and [17] in various batch scheduling problems at the production stage. A brief description of AFT will be given in Section 3.…”
Section: Introductionmentioning
confidence: 99%